IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING CARTOON PICTURE AT FIRST SEMESTER OF STIE-SAK ACADEMIC YEAR 2023/2024 - Sukarta Kartawijaya; Al-Padil; Yelnim (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The objectives of this research are (1) to describe in what extend the cartoon picture strategy improve vocabulary mastery at first semester of STIE-SAK academic year 2023/2024, (2) to describe the class situation when cartoon picture is used in vocabulary mastery. Related to the purposes of the study, the resign design used in this study is classroom action research. The participants of the research are all the students at first semester of STIE-SAK academic year 2023/2024 especially students on the accounting major (class 1A1). There are 27 students as the participants. The research will be conducted in two cycles of action. In collecting the data, the researcher will use qualitative and quantitative technique. The qualitative data are got from observation, and fieldnote analysis. The qualitative data are supported by quantitative data that the mean score of students’ pre-test and evaluation on vocabulary mastery. In this action research, the researcher is as the teacher in teaching learning process. Meanwhile, the observer is the English lecturer in STIE-SAK. It is hoped that teaching vocabulary by using cartoon picture can effectively improve students’ vocabulary mastery. From the vocabulary mastery test, the students’ pre-test mean score was 48,80 improve to 64,80 in the first evaluation and improve to 81,40 in the final evaluation. Therefore, it can be concluded that the teaching vocabulary by using cartoon picturecan improve the students’ English vocabulary mastery at first semester of STIE-SAK academic year 2023/2024.